Crustal electric structure of Haiyuan arcuate tectonic region in the northeastern margin of Qinghai-Xizang Plateau, China - 詹 艳 赵国泽 王继军 汤吉 陈小斌 邓前辉 宣飞 赵俊猛 (Acta seismologica sinica, 2005)
Through the analysis and 2-D inversion for the 5 profiles in Haiyuan arcuate tectonic region (105°-107°E, 36°-37.5°N) in the northeastern margin of Qinghai-Xizang Plateau, we have obtained the electric structure within a range of 160 km in width (east-west) and 60 km in depth in the studied area. The results show that the crustal electric structure can be divided into 6 sections, corresponding respectively to Xiji basin (I), Xihuashan-Nanhuashan uplift (II), Xingrenbu-Haiyuan basin (III), Zhongwei-Qingshuihe basin (IV), Zhongning-Hongsibu basin (V) and west-margin zone of Ordos (VI) from the southwest to the northeast. The crustal electric structure is characterized by a broom-shaped pattern, which scatters to the northwest and shrinks to the southeast. The structures in the top part of Haiyuan arcuate tectonic region are complete and large, however, they diminish from the arc top to the northwest and southeast ends. In the depth from 0 km to 10 km, the resistivity is high in the sections II and VI, but relatively low in the other four sections, showing a similar pattern of basin depression. The electrical basement in the section III is the deepest, displaying a "dustpan" shape that is deep in the southwest and shallow in the northeast. A series of discontinuous zones with high conductivity exist in the middle-lower crust in Haiyuan arcuate tectonic region, which is possibly related to the moderate and strong earthquakes in the region. The resistivity distribution in the focal area of the 1920 Haiyuan earthquake is significantly heterogeneous with an obviously high conductivity zone near the hypocenter regime.[PUBLICATION ABSTRACT]